IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION STRATEGY ASSISTED BY MEDIA WORD CARDS TO IMPROVE BEGINING READING SKILLS AT TK. KR. IMMANUEL SURABAYA - Ita Christine Mergiwati; Saparso; Elika Dwi Murwani, Sarah Prasasti (Adisam Publisher, 2024)
This research aims to determine the implementation of differentiated instruction strategy assisted by word card media to improve the ability of beginning reading at TK. Kr. Immanuel Surabaya. This research was conducted on group B students totalling 16 students. This type of research is a classroom action research. The result of the research obtained are the in cycle 1 there were 7 students (43,75%) who experienced learning completeness with the achievement of early reading skills of 51.50%. The results of observations after cycle 1 showed that there were several students who had not yet achieved mastery of beginning reading skills due to lack of alphabetic ability, lack of phonemic ability and lack of appropriate learning methods based on student learning readiness. In the implementation of cycle 2, it was found that a total of 16 students (100%) experienced learning completeness with the achievement of beginning reading skills of (89.40%). The conclusion of this research is that the implementation of differentiated instruction strategy assisted by word card media contributes to improving students' beginning reading skills at TK. Kr. Immanuel Surabaya. This shows that with differentiated learning based on the diversity of students, it has a direct impact on improving the learning ability of these students.